Analytical procedures in volatile business entities audit context - Pečiūrienė, Aleksandra (Buhalterinės apskaitos teorija ir praktika, 2014)
Evolution of the Lithuanian auditing system recently has been influenced by the European Union picked and chosen process of auditing internationalization. Today among effective ISA there are standards that outline application of analytical procedures in audit. The increasingly important role is assigned to analytical procedures in the audit of business entities operative under the market economy conditions. The objective of the article is to explore the substance and application of analytical procedures in audit. The contribution of this study is polysemantic.The definition of analytical procedures conception in the ISA, SAS and NAS (National Auditing Standards) has been surveyed. The conclusion is drawn that certain mismatches in the definition of analytical procedures conception in the Lithuanian language weren’t avoided neither in the NAS, nor in the ISA, which have been recently in force in Lithuania. Exploring the application of analytical procedures in the auditing process, such aspects as selection of analytical procedures method and form as well as process sequence should be emphasized. Analytical procedures might serve as “attention directing” or “substantive” procedures. Following the ISA provisions auditors are required to perform analytical procedures in the stages of audit planning and forming of overall conclusion. Performing of analytical procedures at the audit testing stage is requested, but not required. Considering that, timing and purposes of analytical procedures are generalized.Analysis of application of analytical procedures as sufficiently significant and effective audit instrument in audit practice is performed. It became as such because in modern audit more and more attention is paid to design and evaluation of accurateness of the auditor’s expectations. Namely the accurateness of expectations should be considered as the measure of analytical procedures effectiveness. The role of analytical procedures in evaluation of a client going concern is emphasized.Dynamics of the number of Lithuanian auditors and audit firms as well as revenue from audit for the period of 2003-2012 years allow anticipating more comprehensive appliance of analytical procedures in audit practice. Consequently, it is expedient to follow the applied researches conducted by foreign specialists in the field of analytical procedure performance in audit on purpose to ascertain the role of analytical procedures as audit efficiency and quality ensure instrument in the Lithuanian audit praxis.
Keywords: analytical procedures; audit; audit standards